Trang chủ » Hỏi đáp » Môn Toán gải phương trình a) (x-1)^3-x(x-1)^2=5x(2-x)-11(x+2) b) (x-2)^3+(3x-1)(3x+1)=(x+1)^3 20/02/2024 gải phương trình a) (x-1)^3-x(x-1)^2=5x(2-x)-11(x+2) b) (x-2)^3+(3x-1)(3x+1)=(x+1)^3
Giải đáp: $\begin{array}{l}a)x \in \emptyset \\b)x = \dfrac{{10}}{9}\end{array}$ Lời giải và giải thích chi tiết: $\begin{array}{l}a){\left( {x – 1} \right)^3} – x{\left( {x – 1} \right)^2} = 5x\left( {2 – x} \right) – 11\left( {x + 2} \right)\\ \Leftrightarrow {x^3} – 3{x^2} + 3x – 1 – x\left( {{x^2} – 2x + 1} \right)\\ = 10x – 5{x^2} – 11x – 22\\ \Leftrightarrow {x^3} – 3{x^2} + 3x – 1 – {x^3} + 2{x^2} – x\\ = – 5{x^2} – x – 22\\ \Leftrightarrow – {x^2} + 2x – 1 = – 5{x^2} – x – 22\\ \Leftrightarrow 4{x^2} + 3x + 21 = 0\\ \Leftrightarrow 4{x^2} + 2.2x.\dfrac{3}{4} + \dfrac{9}{{16}} + \dfrac{{327}}{{16}} = 0\\ \Leftrightarrow {\left( {2x + \dfrac{3}{4}} \right)^2} + \dfrac{{327}}{{16}} = 0\left( {vn} \right)\\Vay\,x \in \emptyset \\b){\left( {x – 2} \right)^3} + \left( {3x – 1} \right)\left( {3x + 1} \right) = {\left( {x + 1} \right)^3}\\ \Leftrightarrow {x^3} – 3.{x^2}.2 + 3.x{.2^2} – {2^3} + 9{x^2} – 1\\ = {x^3} + 3{x^2} + 3x + 1\\ \Leftrightarrow {x^3} + 3{x^2} + 12x – 9 = {x^3} + 3{x^2} + 3x + 1\\ \Leftrightarrow 9x = 10\\ \Leftrightarrow x = \dfrac{{10}}{9}\\Vay\,x = \dfrac{{10}}{9}\end{array}$ Trả lời
a)x \in \emptyset \\
b)x = \dfrac{{10}}{9}
\end{array}$
a){\left( {x – 1} \right)^3} – x{\left( {x – 1} \right)^2} = 5x\left( {2 – x} \right) – 11\left( {x + 2} \right)\\
\Leftrightarrow {x^3} – 3{x^2} + 3x – 1 – x\left( {{x^2} – 2x + 1} \right)\\
= 10x – 5{x^2} – 11x – 22\\
\Leftrightarrow {x^3} – 3{x^2} + 3x – 1 – {x^3} + 2{x^2} – x\\
= – 5{x^2} – x – 22\\
\Leftrightarrow – {x^2} + 2x – 1 = – 5{x^2} – x – 22\\
\Leftrightarrow 4{x^2} + 3x + 21 = 0\\
\Leftrightarrow 4{x^2} + 2.2x.\dfrac{3}{4} + \dfrac{9}{{16}} + \dfrac{{327}}{{16}} = 0\\
\Leftrightarrow {\left( {2x + \dfrac{3}{4}} \right)^2} + \dfrac{{327}}{{16}} = 0\left( {vn} \right)\\
Vay\,x \in \emptyset \\
b){\left( {x – 2} \right)^3} + \left( {3x – 1} \right)\left( {3x + 1} \right) = {\left( {x + 1} \right)^3}\\
\Leftrightarrow {x^3} – 3.{x^2}.2 + 3.x{.2^2} – {2^3} + 9{x^2} – 1\\
= {x^3} + 3{x^2} + 3x + 1\\
\Leftrightarrow {x^3} + 3{x^2} + 12x – 9 = {x^3} + 3{x^2} + 3x + 1\\
\Leftrightarrow 9x = 10\\
\Leftrightarrow x = \dfrac{{10}}{9}\\
Vay\,x = \dfrac{{10}}{9}
\end{array}$